Efektivitas Terapi Musik Instrumental terhadap Nyeri Pada Pasien Pasca Operasi Orif Fraktur Ekstremitas Bawah di RSUD Cileungsi - Chotimah, Chusnul; Sahrudi, Sahrudi; Rudana, I Wayan (Universitas Malahayati, 2025)
ABSTRACT Fracture is a term for the loss of bone continuity, either in whole or in part, which is determined based on the type and extent, usually caused by trauma or physical exertion. One of the treatments is Open Reduction Internal Fixation (ORIF) which aims to mobilize and repair broken bone fragments with several surgical procedures. One of the body's responses after surgery is pain, a physiological mechanism aimed at protecting itself. This study was conducted for effective non-pharmacological treatment to help reduce pain intensity. Classical music therapy is a non-pharmacological effort to improve physical and mental quality with stimuli containing rhythm, song, and harmony which is a work that is useful for reducing anxiety, pain, stress and creating a positive mood. The research used is quantitative research, the design used is